(untitled) (The Research of Medical Science Review, 2024)
Iodine deficiency disorder (IDD) is one of the major disorders in under developed countries. Despite of various interventions, including universal salt iodization, IDD is significantly persistent which might be due to inadequate knowledge, poor attitude, and practice of iodized salt consumption. This study was conducted to determine the knowledge, attitude and practices of community regarding iodized salt consumption and its association with blood pressure among women residing in karma city. This was a cross-sectional study with the sample size of 300 households which was randomly selected and was divided into iodized and non-iodized salt consuming groups. A pre-designed questionnaire was used to determine the knowledge, attitude and practice toward iodized salt consumption. Rapid test kit was used to measure the iodine concentration in household salt samples. Digital blood pressure apparatus was used to measure the systolic and diastolic pressure of respondents. The data was consisted of socio demographic, educational status, anthropometric parameters, blood pressure and knowledge, attitude and practice about iodized salt consumption. This study result shows that the majority female’s educational status was intermediate and above. Iodized salt consumption was significantly correlated with knowledge, attitude and practices (p<0.05) of the respondents. A highly significant (p<0.001) correlation was recorded for the educational status in relation to knowledge about iodized salt. The respondent’s educational profile was also significantly (p<0.05) correlated with positive attitude and practice. Systolic and diastolic blood pressure was also significant correlated (p<0.05) with iodized salt consumption. This study concluded that mass media awareness is required regarding the iodized salt consumption. In addition, monitoring of the field for ensuring iodization of salt is also important.